Quantifying the influences of climate change and human activities on the grassland in the Southwest Transboundary Basin, China. (1st October 2022) - Zhou, Zehui; Jin, Jiaxin; Yong, Bin; Yu, Lei
Abstract: The Southwest Transboundary Basin (STB), which contains a part of the Tibetan Plateau and Southwest China, covers a large area of grassland that has been experiencing significant climate change (Cc) and human activities (Ha). However, variabilities of the grasslands and respective contributions of the drivers have not been fully understood. In this study, we quantitatively investigated the influences of Cc and Ha on the grasslands from 1982 to 2015 across the STB, using residual analysis, trend analysis, and partial correlation analysis. Particularly, vapor pressure deficit (VPD), which is increasingly paid attention to in current studies, was included in our analysis as a critical driver of alpine grasslands. Additionally, a new method, pure climate-induced grassland pixel, which combined the coefficient of variation, was proposed to significantly improve the pixel purity with higher coefficient correlation and lower error and bias. Results show that changes in the climate play an important role in the grassland coverage of STB during 1982–1999 and 2000–2015, while Ha only had a relatively weak negative impact on grassland during 2000–2015, mainly in the Lancang River Basin. Specifically, the grasslands showed an increasing trend in 1982–1999, dominated by climate change with a contribution rate of 80.87%. Temperature had the greatest contribution, followed by VPD and precipitation in this period. On the contrary, the grasslands showed a decreasing trend in 2000–2015, dominated by both Cc and Ha with the contributions of 53.16% and 46.84%, respectively. The findings of this study provide a valuable reference for future ecological restoration in other similar alpine regions. Highlights: A new method was proposed to distinguish climate change and human activities. Vapor pressure defect was introduced in this study. Climate change dominates the change of grassland NDVI in the STB. Temperature restored the grassland in 1982–1999, VPD depressed it in 2000–2015. An increasing (1982–1999)-decreasing (2000–2015) pattern in grassland change in the STB.